Non-invasive multispectral optoacoustic tomography resolves intrahepatic lipids in patients with hepatic steatosis - Fasoula, Nikolina Alexia; Karlas, Angelos; Prokopchuk, Olga; Katsouli, Nikoletta; Bariotakis, Michail; Liapis, Evangelos; Goetz, Anna; Kallmayer, Michael; Reber, Josefine; Novotny, Alexander; Friess, Helmut; Ringelhan, Marc; et al. (Photoacoustics, 2023)
Hepatic steatosis is characterized by intrahepatic lipid accumulation and may lead to irreversible liver damage if untreated. Here, we investigate whether multispectral optoacoustic tomography (MSOT) can offer label-free detection of liver lipid content to enable non-invasive characterization of hepatic steatosis by analyzing the spectral region around 930 nm, where lipids characteristically absorb. In a pilot study, we apply MSOT to measure liver and surrounding tissues in five patients with liver steatosis and five healthy volunteers, revealing significantly higher absorptions at 930 nm in the patients, while no significant difference was observed in the subcutaneous adipose tissue of the two groups. We further corroborated the human observations with corresponding MSOT measurements in high fat diet (HFD) - and regular chow diet (CD)-fed mice. This study introduces MSOT as a potential non-invasive and portable technique for detecting/monitoring hepatic steatosis in clinical settings, providing justification for larger studies.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Lipid imaging; Metabolism; Molecular imaging; MSOT; NAFLD; Non-alcoholic fatty liver disease; Photoacoustics